Studying the Physical State of Phages Using Dynamic Light Scattering (DLS) - Shirvani, Hanieh (2024)
Bacteriophages are viruses that infect bacteria and have the potential to serve as an alternative to antibiotic treatments for illnesses caused by multidrug-resistant bacteria. However, there remains a critical need to develop improved tools for monitoring their stability and bioactivity. Dynamic light scattering (DLS) may offer several advantages over plaque assay for determining phage stability, such as being quicker, more effective, and less damaging. This method measures the Brownian motion of phages in solution caused by bombardment from solvent molecules and links this motion to particle size. Our goal was to investigate whether DLS can be used in phage research and to examine the effect of different treatments on phages physical state. For this purpose, we examined two phages, T4 and PRD1, with their respective host strains of E. coli DMS616 and Salmonella enterica DS88. We used DLS to monitor the sizes of phage particles and investigate the changes triggered by sonication and heating. Both methods led to aggregation and an increase in the z-average. Furthermore, the sonication method caused the denaturation of phages and the formation of multiple sharp peaks. Our studies showed that DLS can be used to investigate the physical state of phages. By examining the correlation coefficient versus time plot, it was observed that the purified samples of intact phage particles had an intercept close to 1. Samples with intercepts significantly higher or lower than 1 indicated an underlying issue with the data, such as aggregation. Multiple shoulders indicated a heterogeneous sample. The intensity-weighted distribution provided the most accurate particle size measurements for monodisperse samples. However, for polydisperse samples, the volume distribution offered a better representation of the contribution of different particle sizes to the overall sample volume.